The theory of linguistic relativity and its relationship to the learning of english as a foreign language - Naranjo Vaca, Ashley de Janeira (2024)
The Theory of Linguistic Relativity proposes that there is a relationship between language and the way we perceive our reality. That is why each language has its own expressions and therefore specific patterns of thought. In this particular setting, the project “The Theory of Linguistic Relativity and its Relationship to the Learning of English as a Foreign Language” is aimed to analyze the influence of this theory in a foreign language classroom. The methodology used is a qualitative approach to have a broad overview of the Theory of Linguistic Relativity. This was gained from bibliographic sources, discourse analysis, and people who had first-hand experience in learning a foreign language. They are 4th-semester students of “Pedagogía de los Idiomas Nacionales y Extranjeros” major from Riobamba-Chimborazo. The main insights of the study demonstrate that the perception of reality is linked to language, due to its background. When comparing English and Spanish, it is evident that there are different linguistic aspects and thoughts between both languages. These differences produce confusion when a foreign speaker does not know how to think in the target language. For this reason, it is recommended to learn about the theory of linguistic relativity and try to acquire the new language using own expressions associated with thought in order to be as close to a native speaker as possible.